2016
DOI: 10.1093/jxb/erw423
|View full text |Cite
|
Sign up to set email alerts
|

Genetic factors underlying boron toxicity tolerance in rice: genome-wide association study and transcriptomic analysis

Abstract: HighlightGenetic factors associated with boron toxicity tolerance in rice were explored through an integrated approach combining genome-wide association study and transcriptomics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 72 publications
4
13
0
Order By: Relevance
“…Necrosis of leaves and decreased growth was previously reported in rice under excess Mn conditions in hydroponics experiments [ 5 , 13 , 18 ]. In addition, we observed significant negative correlation between LDI and all biomass traits ( Table 2 ), similar to previous experiments, in which a diverse rice population was screened for boron toxicity tolerance in rice [ 28 ]. Therefore, cell death symptoms produced by these toxicities can serve as reliable indicators of response to stress.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Necrosis of leaves and decreased growth was previously reported in rice under excess Mn conditions in hydroponics experiments [ 5 , 13 , 18 ]. In addition, we observed significant negative correlation between LDI and all biomass traits ( Table 2 ), similar to previous experiments, in which a diverse rice population was screened for boron toxicity tolerance in rice [ 28 ]. Therefore, cell death symptoms produced by these toxicities can serve as reliable indicators of response to stress.…”
Section: Discussionsupporting
confidence: 88%
“…The 700 k SNP data used for mapping [ 29 ] provided approximately one SNP every 500 bp, covering all 12 chromosomes of rice. SNPs with minor allele frequency of less than 5% were removed [ 24 , 27 , 28 ], resulting in a total of 416741 SNPs. Maker information was retrieved for 271 rice genotypes, which were used for association mapping.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, the DH lines did not differ in shoot Cd concentration ( S2 Fig), whereas in the abovementioned study, a significant phenotypic difference in the DH lines for shoot Cd concentration was reported [38]. In agreement with our results, it has been shown that boron (B) tolerance indicators such as chlorosis and necrosis were not correlated with B uptake and translocation into rice shoots, suggesting that shoot-based tolerance mechanisms played an important role in B toxicity [39]. A possible tolerance mechanism was demonstrated for tolerant cultivars of barley and wheat, in which efflux transporters pump B from the intracellular phase, into the less sensitive apoplast of the leaves [40].…”
Section: Cd-tolerance Related Qtls In Different Populations and Cellusupporting
confidence: 90%